A High Power‐Density, Mediator‐Free, Microfluidic Biophotovoltaic Device for Cyanobacterial Cells. Issue 2 (16th September 2014) - Bombelli, Paolo; Müller, Thomas; Herling, Therese W.; Howe, Christopher J.; Knowles, Tuomas P. J.
<x xml:space="preserve">Abstract</x> Biophotovoltaics has emerged as a promising technology for generating renewable energy because it relies on living organisms as inexpensive, self‐repairing, and readily available catalysts to produce electricity from an abundant resource: sunlight. The efficiency of biophotovoltaic cells, however, has remained significantly lower than that achievable through synthetic materials. Here, a platform is devised to harness the large power densities afforded by miniaturized geometries. To this effect, a soft‐lithography approach is developed for the fabrication of microfluidic biophotovoltaic devices that do not require membranes or mediators. Synechocystis sp. PCC 6803 cells are injected and allowed to settle on the anode, permitting the physical proximity between cells and electrode required for mediator‐free operation. Power densities of above 100 mW m‐2 are demonstrated for a chlorophyll concentration of 100 μM under white light, which is a high value for biophotovoltaic devices without extrinsic supply of additional energy.